2008
DOI: 10.1519/jsc.0b013e31817bd4e8
|View full text |Cite
|
Sign up to set email alerts
|

Trekking Poles Increase Physiological Responses to Hiking Without Increased Perceived Exertion

Abstract: Trekking poles are used by hikers for improved stability and lowered leg fatigue due to increased upper body muscle involvement. However, the weight of the poles and exaggerated upper body movement when using poles may increase total energy expenditure at a given walking speed. Few studies have investigated the physiological responses of hiking with trekking poles outside the laboratory setting. The purposes of this study were to determine if trekking poles altered physiological responses to hiking on varied t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 9 publications
0
29
1
Order By: Relevance
“…3,9 However, the whole-body OMNI scale did not show a difference between the two conditions in the present study. The experimental speed in the present study was equivalent to approximately 90-110 m/min.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…3,9 However, the whole-body OMNI scale did not show a difference between the two conditions in the present study. The experimental speed in the present study was equivalent to approximately 90-110 m/min.…”
Section: Discussioncontrasting
confidence: 79%
“…1 Many studies have reported that a difference between NW and normal level walk-ing (LW) is the energy expenditure involved. [2][3][4][5][6][7] ; when NW and LW are conducted at a certain speed, oxygen uptake (VO 2 ) and heart rate (HR) are higher in NW. The researchers conducting these studies concluded that the reason for this difference is that NW involves many muscles of the upper limbs.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, during maximal speed Nordic Walking the Borg RPE was very low in every group (see Table 3) as on recent study by Schiffer et al (2009) in experienced Nordic Walkers. Saunders et al (2008) found that trekking poles increase physiological responses to hiking without increased perceived exertion. The relationship between Borg RPE with VO 2 and HR was not significant (P>0AE05).…”
Section: Intensity Of Nordicmentioning
confidence: 99%
“…The increased cardiovascular demand was likely to support the greater muscular activity in the upper extremities, as was observed in the triceps brachii. In contrast, some studies 32 34 report increments in the subject’s EE when using trekking poles during walking. Porcari et al 31 and Saunders et al 32 suggest that the increase of HR, VO 2 and EE with the use of trekking poles is due to additional involvement of upper body muscle groups.…”
Section: Introductionmentioning
confidence: 96%
“…The use of trekking poles is relatively recent among those who pursue competitive walking and mountain walking, but during the last decade poles are used more and more for walking on field tracks 6 10 16 . Some of the benefits that have been cited in favor of the use of trekking poles are impact reduction 4 19 , walking instability reduction and fatigue reduction while walking with load carriage 21 28 32 . However, most of the studies performed until now 5 17 18 20 34 have analyzed walking under laboratory conditions and hence lack results that may help in understanding the effects of trekking pole use in load carriage while walking in field conditions.…”
Section: Introductionmentioning
confidence: 99%